Percutaneous ultrasound-guided radiofrequency ablation for patients with liver metastases from gastrointestinal stromal tumors - Li Liu; Bing Wang; Zhong-Yi Zhang; Song Wang; Hao Wu; Hong Wang; Wei Wu; Kun Yan; Wei Yang (International Journal of Hyperthermia)
Objectives This study aimed to analyze the survival outcomes and prognostic factors of radiofrequency ablation (RFA) for liver metastases from gastrointestinal stromal tumors (GISTs).Methods Between March 2011 and November 2022, 34 patients (16 males; age range, 25–72 [median age, 52.5] years) who underwent RFA for liver metastasis from GISTs were included. The mean maximum diameter of metastatic lesions was 2.4 ± 1.0 (range, 1.1–5.2) cm. Survival curves were constructed using the Kaplan–Meier method and compared using the log-rank test. Multivariate analyses were performed using a Cox proportional hazards model.Results For 79 lesions among 34 patients, all targeted lesions were completely ablated. The mean hepatic progression-free survival (HPFS) period was 28.4 ± 3.8 (range, 1.0–45.7) months. The 1-, 3-, and 5-year HPFS rates were 67.2%, 60.5%, and 20.2%, respectively. Based on the univariate analysis, the number of metastatic tumors and tyrosine kinase inhibitors(TKI) therapy before RFA were prognostic factors for HPFS. Multivariate analysis showed that pre-RFA TKI therapy was associated with a better HPFS(p = 0.030). The mean overall survival (OS) period was 100.5 ± 14.1 (range, 3.8–159.5) months and the 1-, 3-, and 5-year survival rates were 96.9%, 77.1%, and 58.7%, respectively. Both univariate and multivariate analysis indicated that extrahepatic metastasis before RFA (p = 0.044) was a significant prognostic factor for OS.Conclusions Liver metastases from GIST exhibit relatively mild biological behavior. RFA is safe and effective, particularly in patients without pre-RFA extrahepatic metastases. Patients received targeted therapy before RFA can obtain an extended HPFS.